Comments on the text by Luis Roberto Cardoso de Oliveira: Ethical-Moral Rights and Conflict Management - Azaola Garrido, Elena (2023)
In this text, I propose to explore some ideas concerning the body of work developed by Luis Roberto Cardoso de Oliveira in recent years and synthesized in a newly-published text entitled “Ethical-Moral Rights and Conflict Management”.